Impact of Islam on the History of Karnataka - Dr. V. VENKATESH, (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
Karnataka has welcomed and accommodated in her midst quite a few religions of people from elsewhere, which shows its traditional generosity. These religions in their turn have also contributed towards her rich and diverse culture. Soon after Islam’s propagation in Arabia, as Arabs were trading at the ports of Karnataka like Mangalore, Bhatkal and few others, Islam entered Karnataka in the 7th century A.D. The Persian ruler Khusru-II established diplomatic relations with King